Analysis of The Implementation of The Excavation Work of Blasting Stone in The Quarry For Rockfill Pile of The Beringin Sila Dam Construction Work Project Package-1 Sumbawa Regency, NTB. - Ikhwan Sholihuddin; Adi Prawito (Journal of World Conference (JWC), 2022)
Embankment dams based on the grain size of the embankment material used are divided into 2 types, namely rock filled dams and earth fill dams. The Beringin Sila Dam is a random and rock fill dam with an upright core which is in the process of being built by stockpiling materials such as stone, gravel, clay, and soil. Blasting is an activity of breaking up a material (rock) using explosives or the process of an explosion, in blasting one of the important things that must be considered is the fragmentation of rock resulting from blasting. The method is carried out by observing the realization in the field and analyzing project data. The purpose of this study was to determine the productivity of heavy equipment, to analyze the realization costs of excavation and heap of blasted rock at the quarry location. The results of this study indicate that the productivity of drilling tools for drilling tools, with the Crawler Rock Drill (CRD) tool, it gets 5 holes/hour, while with the Hydraulic Crawler Drill (HCR) it gets 4 holes/hour. Productivity of loading and unloading equipment on excavation work and blasting heaps of rock at the quarry location, with an average of 25 units of transportation equipment and 4 units of CAT 330 excavator as loading equipment. For loading equipment, the production yield is 41.40 m3/hour, while for transportation equipment the production yield is 6.62 m3/hour. The realization cost for excavation work and rock heap from blasting at the quarry location in July – September required a cost of Rp.11,124,373,500.00 including the cost of wages, materials, and tools.